ANALYSIS OF ISLAMIC MARKETING STRATEGIES IN INCREASING THE VOLUME OF SALES OF YOUNG ENTREPRENEURS IN BIMA CITY - Mulmansyah; Umar, Umar Sagaf; Ibrahim (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2025)
The purpose of this research is to find out about how the application of Islamic economic principles in marketing strategies carried out by young entrepreneurs in Bima City. As well as to understand how the application of SWOT Analysis on Islamic marketing. The method used in this research is qualitative method. The data sources used in this study are primary data sources and secondary data sources, where primary data sources are obtained directly from the object of research by conducting interviews, in this case the owner of the Yuank Canteen is the object of research. while secondary data sources are obtained from sources directly related to research such as journals, books, reports and so on. The results showed that the study of the Yuank Canteen in Bima City showed that Islamic economic principles (justice, honesty, prohibition of usury / gharar) were successfully integrated into marketing strategies through innovations such as “Transparent Menu” and alms promotion. SWOT analysis proved effective despite the challenges of competition and consumer literacy. The success of the Yuank Canteen proves that sharia marketing can be a competitive advantage, but it needs stronger ecosystem support. Business success in Islam is not only judged by profit, but also blessings and social impact, making it spiritually and practically relevant.